Neural Regulation of Interactions Between Group 2 Innate Lymphoid Cells and Pulmonary Immune Cells - Chen, Weiwei; Shu, Qiang; Fan, Jie (Frontiers in Immunology, 2020)
Emerging evidence supports the involvement of nervous system in the regulation of immune responses. Group 2 innate lymphoid cells (ILC2), which function as a crucial bridge between innate and adaptive immunity, are present in large numbers in barrier tissues. Neuropeptides and neurotransmitters have been found to participate in the regulation of ILC2, adding a new dimension to neuroimmunity. However, a comprehensive and detailed overview of the mechanisms of neural regulation of ILC2, associated with previous findings and prospects for future research, is still lacking. In this review, we compile existing information that supports neurons as yet poorly understood regulators of ILC2 in the field of lung innate and adaptive immunity, focusing on neural regulation of the interaction between ILC2 and pulmonary immune cells.